The Prevalence, Rainbow of Histological Features and Initial Clinical Presentation of Post-Transplant IgA Nephropathy - Maryam, Hanzla; Hussain, Mudassar; Afzal, Aurangzeb; Hassan, Usman; Ishtiaq, Sheeba (Pakistan Journal of Medical & Health Sciences, 2024)
Background: IgA nephropathy is the most common primary glomerulopathy which is characterized by the presence of prominent IgA deposits in the mesangial regions. Aim: To compare the clinical and histological features of pre and post- transplant IgA nephropathy patients. Methods: A descriptive retrospective study. Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, between 1st January 2016 and 30th September 2022. Forty eight cases of pre-transplant and 20 cases of post-transplant IgA nephropathy were enrolled. The biopsies included at least one core submitted in 10% buffered formalin and one core in normal saline. The formalin-fixed tissue was embedded in paraffin and cut at 4mm thickness, followed by staining with hematoxylin, eosin, PAS, JMS, and Trichrome stains. Immunofluorescence was performed on the tissue in normal saline. All biopsy was evaluated for the MEST-C score. Patients were also evaluated for proteinuria and hematuria; we categorized hematuria as mild (3-20 red blood cells per microliter of urine), moderate (20-50 red blood cells per microliter of urine), and severe (above 50 red blood cells per microliter of urine). Proteinuria was divided as sub-nephrotic range proteinuria and nephrotic range proteinuria. Results: The 90% of patients were male and 10% were female, and the highest proportion of post-transplant patients (45%) were between 35 and 45 years old. 25% of patients experienced significant hematuria, and an equal percentage (25%) experienced mild to moderate hematuria. 40% of patients experienced nephrotic range proteinuria, and 20% had sub-nephrotic range proteinuria. Histological evaluation of renal biopsies of these patients demonstrated M1 lesions in 75% of patients, S1 lesions in 65% of patients, and T1 lesions in 45% of patients. Among the patients with pre-transplant IgA nephropathy, 70% were male, 27% were female, and 45% of patients were below the age of 25. 30% of patients experienced severe hematuria, while 36% experienced mild to moderate hematuria. 42% of the patients had nephrotic range proteinuria and 40% had sub-nephrotic range proteinuria. Histological evaluation of their renal biopsies demonstrated M1 lesions in 94% of the pre-transplant patients, S1 lesions in 90%, and E1 lesions in 27% of cases. Practical Implication: The high significance in implementing the service care delivery to the kidney transplant patient as by critically assessing the urine testing predictors, biopsy results and patient gender as well as age the IgA nephropathy risk can be reduced. Conclusion: The combination of proteinuria and hematuria assessment could provide an important insight of disease recurrence in kidney transplant patients. Moreover, the results emphasize the importance of carefully monitoring transplant patients with high M-scores and T-scores, especially those with S1 scores, to ensure early detection and management of disease recurrence.